Recommendations for The Selection and Processing of Statistical Methods in Pedagogical Research - Mansurova Nodira Husanbayevna; Yodgarov Samad Zhurayevich; Rakhmatova Sevinch Kholbekovna (Genius Journals, 2023)
The article considers an algorithm for selecting a statistical criterion for testing statistical hypotheses depending on the type of available data and their distribution. The presented material provides general recommendations on choosing the most appropriate method of data analysis for the most common situations.
Keywords: data type; statistical criteria